2018
DOI: 10.1002/smll.201802764
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Stable and Self‐Driven Perovskite Photodiodes with High On/Off Ratio and Swift Photoresponse

Abstract: Recent years have witnessed rapid developments in organic-inorganic hybrid perovskites, among which 2D Ruddlesden-Popper (RP) perovskites stand out due to their outstanding ambient stability. In photodetector applications, 2D RP perovskites are mostly limited to lateral device configuration because of their preferred in-plane charge transportation within quantum well structures. In this work, the low-temperature solution construction of 2D RP perovskite-based photodiodes in vertical device architecture is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The PL decays of both PEA and TEA samples can be best fitted by a biexponential function in Equation :It=A1exptτ1+A2exptτ2where A 1 and A 2 are the amplitudes, τ 1 and τ 2 are the PL decay times. According to our previous studies in 2D perovskites,] τ 1 corresponds to the PL quenching from fast nonradiative recombination which is induced by defects or impurities introduced during preparation of grains or interphase charge transfer. The slower time constant τ 2 represents radiative recombination of the charge carriers.…”
Section: Photovoltaic Performance Parameters Of Pea2ma3pb4i13‐ and Tementioning
confidence: 99%
See 3 more Smart Citations
“…The PL decays of both PEA and TEA samples can be best fitted by a biexponential function in Equation :It=A1exptτ1+A2exptτ2where A 1 and A 2 are the amplitudes, τ 1 and τ 2 are the PL decay times. According to our previous studies in 2D perovskites,] τ 1 corresponds to the PL quenching from fast nonradiative recombination which is induced by defects or impurities introduced during preparation of grains or interphase charge transfer. The slower time constant τ 2 represents radiative recombination of the charge carriers.…”
Section: Photovoltaic Performance Parameters Of Pea2ma3pb4i13‐ and Tementioning
confidence: 99%
“…According to our previous studies in 2D perovskites, [31] the exciton diffusion length (L D ) was measured as shown in Figure 4b with the inset illustrating the measurement setup. According to our previous studies in 2D perovskites, [31] the exciton diffusion length (L D ) was measured as shown in Figure 4b with the inset illustrating the measurement setup.…”
Section: Doi: 101002/advs201900548mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, 2D and quais‐2D perovskites have been used in FPDs due to their increased robustness to moisture and solution process. For example, Liang and co‐workers reported 2D (PEA) 2 MA 3 Pb 4 I 13 perovskites by the low‐temperature solution process, in which 3D phases were inserted into 2D perovskite, enhancing cross‐plane charge transfer . Moreover, the 2D perovskites were utilized to fabricate vertically structured photodetector which exhibited a high on/off ratio and swift photoresponse.…”
Section: Metal Halide Perovskitementioning
confidence: 99%